Peningkatan Kapasitas dan Penguatan Sistem Pelaporan Juru Pemantau Jentik Dalam Penerapan “1 Rumah 1 Jumantik” di Komunitas: Era Adaptasi Baru Covid-19 - Kusumaratna, Rina Kurniasri; Alam, Mohammad Nahdiyin Mangku; Supriyadi, Anisah; Suriyani , Suriyani (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Environmental health is an essential part of public health efforts. Interaction between humans and the environment could influence each other. One of the impacts has the emergence of health problems related to vectors, one of the vectors of the disease is known as mosquitoes. The purpose of the service is to increase capacity and strengthen the reporting system in applying the concept of "1 Home 1 Jumantik" of 89 jumantik health cadres. It started with a situation analysis and problem evaluation and continued with problem-solving and capacity building for health cadres. As a final activity, we created and designed an e-reporting using google-form and tested it in 3 pilot RWs at the Bintaro Health Center, South Jakarta. As a result, the skill competency of cadres was increased in using the e-reporting form for larva monitoring to support the movement “1 Home 1 Jumantik”. As we hope that health cadres could become agents of change to socialize the form to all household residents. However, some cadres still have problems using the application and reading the results. Evidence of refresher activities based on the objective score of knowledge among cadres showed an increase based on the pre-test scores from 64 and post-test to 90 (26%). In the current pandemic situation, the need for up-to-date and fast reporting including activating and implementing the "1R 1J Movement" is the right solution. Therefore, it's necessary to introduce the electronic technology-based reporting system support to health cadres and the community at the household level to become independent and engage to solve their health problems.